2003
DOI: 10.1292/jvms.65.535
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of Bovine Blood and Milk Polymorphonuclear Leukocytes after Ozone Gas Administration In Vitro

Abstract: ABSTRACT. To determine the effects of ozone on the phagocytosis of bovine polymorphonuclear leukocytes (PMNs), ozone gas was administered in vitro on the blood and milk of healthy lactating cows, cows with acute mastitis, and cows with milk fever. In the blood of healthy dairy cattle, although there was no significant effect of ozone gas on the viability of the leukocytes, phagocytosis of PMNs significantly decreased. In contrast, ozone gas administration in vitro significantly increased phagocytosis of PMNs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…Host response to biofilm plays a critical role in the pathogenesis of periodontitis [47]; many proinflammatory cytokines are involved in inflammation and bone loss [48]. Resolution of inflammation may be supported by ozone; ozone was found to inhibit NFκB-pathways [49] as well to increase the phagocytotic capacity of bovine PMNs in inflammation [50]. Ozone was shown to be toxic to human oral epithelial cells and gingival fibroblasts but in a lower extent than different antimicrobials [51].…”
Section: Discussionmentioning
confidence: 99%
“…Host response to biofilm plays a critical role in the pathogenesis of periodontitis [47]; many proinflammatory cytokines are involved in inflammation and bone loss [48]. Resolution of inflammation may be supported by ozone; ozone was found to inhibit NFκB-pathways [49] as well to increase the phagocytotic capacity of bovine PMNs in inflammation [50]. Ozone was shown to be toxic to human oral epithelial cells and gingival fibroblasts but in a lower extent than different antimicrobials [51].…”
Section: Discussionmentioning
confidence: 99%
“…The high cure rate of acute mastitis in dairy cows is attributable to ozone's characteristic feature of inducing less release of endotoxin. The effects of ozone on immunity have been reported [2,18,19]; ozone may downregulate the cytotoxic activity of immunocytes.…”
mentioning
confidence: 99%
“…It was reported that treatment with ozone released fewer endotoxins in the milk than treatment with antibiotics; further, no iatrogenic endotoxic shock occurred as an adverse effect, unlike that in the case of antibiotic treatment [10]. In addition, it has been reported that ozone may result in the downregulation of the cytotoxic activity of immunocytes [1,21,22]. Therefore, we speculated that using ozone water as an irrigation fluid during MIR as the first line of treatment for coliform mastitis was possible to reduce mortality.…”
Section: Discussionmentioning
confidence: 99%